Mastering microsurgery: A novel benchmarking tool for microsurgical training. Issue 2 (February 2022) - Kim, Eunsol; Chawla, Shreya; Ghanem, Ali
Summary: Introduction and objective: The shift of surgical training from apprenticeship model towards competency-based training requires objective assessments of microsurgical skills to achieve mastery. Our objective was to create a novel platform to provide feedback to surgical trainees relative to competency expected at their level of exposure. Methods: A 5-day simulated microsurgery course was run between 2013 and 2016 with 118 participants. Video recordings of end-to-end micro-anastomoses were collected on days 1, 3, and 5, along with analysis of hand motion . Videos were assessed to calculate the QMUL Global Rating Scale (QMUL GRS). Two charts were created to track the acquisition of microsurgical skills. One to plot the number of hand movements and the other for QMUL GRS, against the participants' cumulative number of micro-anastomoses performed. Participant data were used to calculate a skills acquisition line for each quartile, analogous to percentiles on a growth chart. Results: For a cumulative number of 0 prior micro-anastomoses, the GRS score at the 25th, 50th, and 75th percentile was 45.5, 55, and 62, respectively. As the number of cumulative anastomoses increased, there was a distinct increase in the GRS score to 89.5, 93, and 92 for the group with 55–100 previous micro-anastomoses. This was in keeping with a decreased number of hand movements with increasing experience. Conclusion: In conclusion, our tool allows trainees to track where they lie in the skill spectrum relative to prior experience which permits the provision of focused training to trainees at lower percentiles, which has potential to translate to improved clinical outcomes.